The Success of Solar Diesel Minigrids in Bangladesh: A Case Study of Sandwip Island. (December 2016) - Aziz, Shakila; Chowdhury, Shahriar Ahmed; Groh, Sebastian
Abstract: Set-up in 2009, the solar diesel hybrid minigrid in Enam Nahar market in Sandwip Island is the oldest running minigrid of its kind in Bangladesh. Several similar minigrids are under construction in different parts of Bangladesh and the experience from this pioneer minigrid should serve as a valuable source of information for up-coming entrepreneurs as well as for financing organizations and government regulators alike. This minigrid has been considerably successful in terms of customer satisfaction. However, there have also been a multitude of problems with respect to competition from the extension of grid systems by national utility to the same site, as well as in terms of technical matters related to logistics and maintenance in this remote costal environment. These factors are critically reflected within this work and conclusions are drawn for the planning of further minigrids in the country.